Old wine in new bottles? Regulating employee social media use through termination of employment law: A comparative analysis. (December 2018) - O'Rourke, Anne; Pyman, Amanda; Teicher, Julian; van Gramberg, Bernadine
The explosion in social media usage and ease of access to instant communication provided by new technologies presents employers and business with benefits and problems. The literature on new technologies and the workplace is replete with employer unease about employee use of social media. The most prominent of these apprehensions concern what has been described as 'cyberslacking' or 'cyberloafing', and reductions in concentration and workplace productivity. The most common employer response to these concerns is often to engage in employee surveillance or termination of employment. This article examines the latter response. It explores whether new legal principles are emerging from Courts, Tribunals and Commissions adjudicating social media and email dismissal cases or whether they are merely reframing existing laws to adapt to novel workplace situations. We use a comparative approach to address this question, comparing legal cases in Australia, Britain and America. The purpose of this article is to assess if there are any commonalities emerging between the three jurisdictions, or by contrast, whether the law is being shaped by the unique features of each jurisdiction.